PENILAIAN SEJAWAT PADA MATA KULIAH MICROTEACHING SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN DASAR MENGAJAR DI SEKOLAH DASAR - Rizkasari, Elinda (Jurnal Pendidikan Dasar, 2022)
This study aims to describe the application of peer assessment in microteaching lectures for elementary school teacher education. This peer assessment is carried out by students using the assessment instruments and indicators that have been prepared. Peer assessment was carried out by groups that did not conduct teaching simulations. The use of peer assessment is used to provide an understanding of what aspects are assessed in practicing basic teaching skills so that students can adjust to get optimal assessments so that basic teaching skills can be improved. The data analysis technique used is descriptive qualitative. The indicator of the success of this research is marked by the increase in student learning outcomes, especially in the aspect of basic teaching skills that have reached good criteria. The results of this study indicate that the teaching and learning process using peer assessment can improve learning outcomes in microteaching lectures. This is evidenced by an increase in learning outcomes in the psychomotor aspect, namely basic teaching skills. The results of peer assessment are then used as input and consideration in evaluating students in microteaching learning.